The ERK and JNK pathways in the regulation of metabolic reprogramming - Papa, Salvatore; Choy, Pui Man; Bubici, Concetta (Oncogene, 2019)
Most tumor cells reprogram their glucose metabolism as a result of mutations in oncogenes and tumor suppressors, leading to the constitutive activation of signaling pathways involved in cell growth. This metabolic reprogramming, known as aerobic glycolysis or the Warburg effect, allows tumor cells to sustain their fast proliferation and evade apoptosis. Interfering with oncogenic signaling pathways that regulate the Warburg effect in cancer cells has therefore become an attractive anticancer strategy. However, evidence for the occurrence of the Warburg effect in physiological processes has also been documented. As such, close consideration of which signaling pathways are beneficial targets and the effect of their inhibition on physiological processes are essential. The MAPK/ERK and MAPK/JNK pathways, crucial for normal cellular responses to extracellular stimuli, have recently emerged as key regulators of the Warburg effect during tumorigenesis and normal cellular functions. In this review, we summarize our current understanding of the roles of the ERK and JNK pathways in controlling the Warburg effect in cancer and discuss their implication in controlling this metabolic reprogramming in physiological processes and opportunities for targeting their downstream effectors for therapeutic purposes.